Regionalism in Hellenistic and Roman Asia Minor - Gary Reger (Ausonius Éditions, 2007)
Regions and regionalism have been staples of historical analysis for the Greek world for a very long time. What is meant by a region, however, is not always obvious. The contributions in this volume seek to address the question of defining regions and working out the implications of regionalism along different dimensions of analysis for Asia Minor in the Hellenistic and Roman periods. Looking at culture, coinage, political institutions, the papers explore different markers of regional identity, consider ways in which these identities may remain stable or change over time, review the character of the interaction between regional entities and hegemonic powers, and challenge the usefulness in some cases of regional analysis. Questions of ethnicity are also addressed. This volume will be of interest to historians working in Asia Minor and also to anyone concerned with the conceptual questions around regions and regionalism in the Mediterranean world.